Investigation of Flower, Seed and Fruit Structure of Helleborus orientalis Lam. (Ranunculaceae) Taxa - Derviş ÖZTÜRK (ISPEC Journal of Agricultural Sciences, 2020)
In this study, flower morphology, seed and fruit structure of Helleborus orientalis Lam. (Ranunculacaae) species were investigated. Helleborus L. is a poisonous plant genus with about 20 species spread from the Ranunculaceae family, from Central, Southern and Eastern Europe to the Caucasus borders. Helleborus L. genus is represented by two species in Turkey. These are H. vesicarius Aucher and H. orientalis Lam. species. In our country, "hellebore", known as such, grows naturally in Turkey. H. orientalis is known by local names such as bundle grass, black litter, black harbak, horn grass, calf and danakıran. It is a perennial herbaceous plant. Their bodies are leafless and 60 cm long, and their base leaves are evergreen. It has long petioles, broad leaves, digitate, and its flower structure is symosis. Sepals are greenish white, sometimes purplish, ovate, 20-30 (-35) mm. The average life span of a single flower after fully opening is about 6 days. The flower cover is arranged on two rows, has 5 wide rings on the outside resembling a sepale or a petal, the fruit is permanent, the ones in the inner ring are small, tubular, 2-lipped piece (nectarium). Short anthers on long crest, rarely blunt. Anthers are a group of fruits with several seeded follicles fused at least at the base. Seeds are usually more than 6. Flowering is usually between March and May. The H. orientalis species is generally distributed in the Black Sea Region and its general distribution is over Greece and the Caucasus regions. It is generally found in forest openings and under forest, between 1-2200 meters in scrub habitats. Turkey A2, A3, A4, A5, A6, A7, A8, A9 and B3 shows the distribution frame. The study material was collected from Cicekli plateau of Bilecik province, located in A3 square, on 23.05.2020 and turned into a herbarium material. Morphological studies were examined by making measurements on living samples.